American College of Rheumatology Guidance for the Management of Rheumatic Disease in Adult Patients During the COVID‐19 Pandemic: Version 2. Issue 9 (30th July 2020) - Mikuls, Ted R.; Johnson, Sindhu R.; Fraenkel, Liana; Arasaratnam, Reuben J.; Baden, Lindsey R.; Bermas, Bonnie L.; Chatham, Winn; Cohen, Stanley; Costenbader, Karen; Gravallese, Ellen M.; Kalil, Andre C.; Weinblatt, Michael E.; et al.
Abstract : Objective: To provide guidance to rheumatology providers on the management of adult rheumatic disease in the context of the coronavirus disease 2019 (COVID‐19) pandemic. Methods: A task force, including 10 rheumatologists and 4 infectious disease specialists from North America, was convened. Clinical questions were collated, and an evidence report was rapidly generated and disseminated. Questions and drafted statements were reviewed and assessed using a modified Delphi process. This included asynchronous anonymous voting by e‐mail and webinars with the entire panel. Task force members voted on agreement with draft statements using a 1–9‐point numerical scoring system, and consensus was determined to be low, moderate, or high based on the dispersion of votes. For approval, median votes were required to meet predefined levels of agreement (median values of 7–9, 4–6, and 1–3 defined as agreement, uncertainty, or disagreement, respectively) with either moderate or high levels of consensus. Results: To date, the task force has approved 80 guidance statements: 36 with moderate and 44 with high consensus. These were combined, resulting in 27 final guidance statements. Conclusion: These guidance statements are provided to promote optimal care during the current pandemic. However, given the low level of available evidence and the rapidly evolving literature, this guidance is presented as a "living document, " and future updates are anticipated.